The Relation between Gender, Reasons to Participate in STEM-Related Subjects, Programs and The University Supports On First-Year University Student’s Satisfaction: A Structural Equation Model - Ikmanda Nugraha; Tatang Suratno; Asep Kadarohman; Ari Widodo; I Gusti Darmawan (Journal of Science Learning, 2020)
First-year student's satisfaction has considered an important factor in the quality education offered by the university program. The objective of this study is to investigate the relationship among gender, a reason to participate in STEM-related subjects, program, and the university support on first-year student's satisfaction of STEM learning. The methods used in this study surveyed student's satisfaction using adapted interest and recruitment in the science questionnaire (IRIS Q) instrument. The questionnaire comprised question items covering school science experiences, sources of inspiration for the choice of education, expectations for future job, first-year experiences as a STEM student, and attitudes to gender equity in STEM. A total of 448 students, first-year students from STEM-related programs, have participated voluntarily in this study. The structural equating model assisted by computer program IBM SPSS Amos 20 was employed to analyze the hypothesized model. The results from the model showed that reason and university support have a positive direct effect on first-year students' satisfaction with STEM learning. From this study, it is suggested for the university to improve first-year student's satisfaction by helping STEM students to develop appropriate expectations of the program, facilitating teaching quality to meet STEM students' learning, and assisting students in developing positive attitudes toward their future carriers.